Sn-containing low-hydrogen induced delayed cracking sensitivity 1500MPa-grade hot forming steel and preparation method and application of Sn-containing low-hydrogen induced delayed cracking sensitivity 1500MPa-grade hot forming steel
By adding Sn elements to the thermoformed steel, the formation of cementite is promoted and the hydrogen trap capacity is improved, and the sensitivity of high-strength thermoformed steel in hydrogen-induced delayed cracking is solved, and the high-strength and low-hydrogen-induced delayed cracking of the material is achieved, thereby reducing production costs.
Patent Information
- Application Number
- CN202411825100.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
AI Technical Summary
High-strength thermoformed steel is prone to hydrogen-induced delayed cracking under the action of hydrogen and stress, resulting in brittle fracture of the material, affecting its application and development.
Adding Sn elements to the thermoformed steel promotes cementite formation, increases the content of pearlite, improves the stability of ε carbides and hydrogen trap capabilities, thereby reducing the sensitivity of hydrogen-induced delayed cracking.
By adding Sn element, the hydrogen-induced delayed cracking sensitivity of the material is reduced by at least 50%, while maintaining high strength, tensile strength ≥1500MPa, elongation ≥10%, and reducing production costs.
Smart Images

Figure CN119615003A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ultra-high strength steel production, and in particular to a Sn-containing 1500MPa grade hot-formed steel with low hydrogen-induced delayed cracking sensitivity, and a preparation method and application thereof. Background Art
[0002] With the rapid development of the automobile industry, lightweight and safety have become the main directions of the development of the automobile industry. High-strength steel can not only achieve lightweight through thinning, but also improve collision safety, and has become the main material for lightweighting in the automobile industry. However, with the continuous improvement of the strength of steel plates, the cold stamping forming performance in the process stage has rapidly declined, and problems such as easy cracking, easy rebound, and poor dimensional accuracy of parts will occur. The emergence of hot forming technology has successfully solved this problem. Hot forming technology combines high-temperature forming with quenching and strengthening through simple alloy composition design, and can obtain parts with a strength level of 1500MPa and above, which perfectly solves the contradiction between ultra-high strength and good formability. At present, major domestic and foreign automobile manufacturers have used this 1500MPa extremely hot forming steel in large quantities in the A / B pillars, bumpers, anti-collision beams and other parts of the automobile body.
[0003] However, as the strength increases, the sensitivity of steel to hydrogen-induced delayed cracking also increases, especially for ultra-high strength steel with a strength greater than 1000MPa, where the sensitivity to hydrogen-induced delayed cracking is more significant, becoming a major problem restricting the application and development of ultra-high strength steel. Hydrogen-induced delayed cracking is a phenomenon in which a material suddenly undergoes brittle fracture after a certain period of time under the action of hydrogen and stress. It is the result of the interaction between the material, hydrogen, and stress. Hydrogen-induced delayed cracking usually occurs suddenly when the applied stress level to the material is significantly lower than its yield strength. It is unpredictable and will cause serious consequences once it occurs.
[0004] To address the hydrogen-induced delayed cracking problem of hot-formed steel, the main measures currently adopted in domestic and foreign patents and literature include adding micro-alloying elements such as Nb, V, and Mo to refine the original austenite grains through solute drag and carbonitride pinning of grain boundaries, while forming carbonitrides to capture hydrogen and inhibit hydrogen diffusion. However, micro-alloying elements such as Nb, V, and Mo are relatively expensive, and adding micro-alloying elements such as Nb, V, and Mo to improve the hydrogen-induced delayed cracking problem will increase the cost of hot-formed steel and reduce the promotion and application of hot-formed steel. Summary of the invention
[0005] The present invention provides a Sn-containing 1500MPa-grade hot-formed steel with low hydrogen-induced delayed cracking sensitivity, and a preparation method and application thereof. By adding Sn elements to the hot-formed steel, the hydrogen trapping capacity can be improved to solve the problem of high hydrogen-induced delayed cracking sensitivity of the current hot-formed steel, while effectively controlling the cost.
[0006] In order to solve the above technical problems, one of the objects of the present invention is to provide a Sn-containing 1500MPa grade hot-formed steel with low hydrogen-induced delayed cracking sensitivity, comprising the following components by mass fraction: C: 0.20wt%-0.23wt%, Si: 0.23wt%-0.27wt%, Mn: 1.0wt%-1.5wt%, Cr: 0.15wt%-0.25wt%, Ti: 0.015wt%-0.050wt%, B: 0.002wt%-0.005wt%, Sn: 0.01wt%-0.12wt%, P: ≤0.015wt%, S: ≤0.005wt%, and the balance is Fe and unavoidable impurities.
[0007] By adopting the above scheme, the present application adds Sn elements to hot-formed steel to promote the formation of cementite, which can increase the content of pearlite in the hot-rolled plate, effectively improve the stability of ε carbide in the hot forming stage, improve the hydrogen trap capacity of carbide, effectively capture hydrogen atoms, and thus reduce the material's hydrogen-induced delayed cracking sensitivity. Compared with adding micro-alloying elements such as Nb, V, and Mo to improve the problem of hydrogen-induced delayed cracking sensitivity, the Sn element added in the present application is more expensive, which reduces the production cost of hot-formed steel and expands the application range of the product.
[0008] As a preferred solution, the mass fraction of Sn in the hot-formed steel is 0.02wt%-0.1wt%. Too high a Sn content will segregate to the original austenite grain boundaries, reduce the grain boundary bonding force, and affect the mechanical properties of the material. Therefore, the present invention optimizes the Sn content to simultaneously improve the mechanical properties of the material and reduce the sensitivity to hydrogen-induced delayed cracking.
[0009] As a preferred embodiment, the following components are included in mass fractions: C: 0.2wt%, Si: 0.27wt%, Mn: 1.4wt%, Cr: 0.16wt%, Ti: 0.015wt%, B: 0.002wt%, Sn: 0.02wt%, P: ≤0.015wt%, S: ≤0.005wt%, and the remainder is Fe and unavoidable impurities.
[0010] As a preferred embodiment, the following components are included in mass fractions: C: 0.21wt%, Si: 0.23wt%, Mn: 1.15wt%, Cr: 0.2wt%, Ti: 0.02wt%, B: 0.003wt%, Sn: 0.1wt%, P: ≤0.015wt%, S: ≤0.005wt%, and the remainder is Fe and unavoidable impurities.
[0011] In order to solve the above technical problems, the second object of the present invention is to provide a method for preparing Sn-containing 1500MPa grade hot-formed steel with low hydrogen-induced delayed cracking sensitivity, comprising the following steps:
[0012] (1) preparing ingredients according to a set element mass percentage, mixing and smelting, and then casting into a billet to obtain a billet;
[0013] (2) heating the blank to perform homogenization treatment;
[0014] (3) hot rolling the homogenized billet;
[0015] (4) Coiling after hot rolling;
[0016] (5) Hot stamping is performed, the heating temperature of hot stamping is 900°C-950°C, and then quenching is performed to room temperature to obtain hot-formed steel.
[0017] As a preferred embodiment, in step (2), the heating temperature for homogenization treatment is 1180°C-1250°C.
[0018] As a preferred embodiment, in step (3), the hot rolling process controls the final rolling temperature to be 780°C-880°C.
[0019] As a preferred embodiment, in step (4), the coiling temperature is 620°C-700°C.
[0020] As a preferred solution, in step (5), the hot stamping holding time is 3 min-5 min.
[0021] In order to solve the above technical problems, the third object of the present invention is to provide a Sn-containing 1500MPa grade hot-formed steel with low hydrogen-induced delayed cracking sensitivity for use in the field of preparing automotive parts.
[0022] As a preferred solution, the automobile accessories are specifically A / B pillars, bumpers, anti-collision beams, etc. of the automobile body.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present application adds Sn element to hot-formed steel to promote the formation of cementite, which can increase the content of pearlite in the hot-rolled plate, effectively improve the stability of ε carbide during the hot forming stage, improve the hydrogen trap capacity of carbide, and effectively capture hydrogen atoms, so that the hydrogen-induced delayed cracking sensitivity of the material is reduced by at least 50%, and the mechanical strength of the hot-formed steel is maintained, with a tensile strength of ≥1500MPa and an elongation of ≥10%.
[0025] 2. The present application adds Sn element to reduce the sensitivity to hydrogen-induced delayed cracking. Compared with the existing method of improving the sensitivity to hydrogen-induced delayed cracking by adding micro-alloying elements such as Nb, V, and Mo, the Sn element added in the present application has a higher cost, which reduces the production cost of hot-formed steel and expands the application range of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 : Tensile stress-strain curves of 1500MPa grade hot-formed steel in Examples 1-2 and Comparative Example 1 of the present invention before and after the hydrogen charging experiment (Note: left - Comparative Example 1; middle - Example 1; right - Example 2).
[0027] Figure 2 : Metallographic structures of Examples 1-2 and Comparative Example 1 of the present invention (Note: left - Comparative Example 1; middle - Example 1; right - Example 2). DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The following Table 1 shows the sources and types of raw materials used in the examples and comparative examples of the present application. Unless otherwise specified, the raw materials used can be obtained commercially, and the same raw materials are used in parallel experiments.
[0030] Example 1
[0031] A Sn-containing low hydrogen-induced delayed cracking sensitivity 1500MPa grade hot-formed steel, the composition and content of which are shown in Table 1 below, including 0.2wt% C, 0.27wt% Si, 1.4wt% Mn, 0.16wt% Cr, 0.015wt% Ti, 0.002wt% B, 0.02wt% Sn, and P≤0.015wt%, S≤0.005wt%, and the balance is Fe and unavoidable impurities. The preparation method thereof comprises the following steps:
[0032] (1) Preparing, smelting and casting into billets according to the set element mass percentages;
[0033] (2) heating the blank to 1200° C. for homogenization;
[0034] (3) hot rolling the homogenized billet, and controlling the final rolling temperature at 800°C;
[0035] (4) coiling at 650°C after hot rolling;
[0036] (5) Hot stamping is performed, specifically, the steel is heated to 930° C. and then kept at this temperature for 5 min, and then quenched to room temperature to obtain hot-formed steel.
[0037] Example 2
[0038] A Sn-containing low hydrogen-induced delayed cracking sensitivity 1500MPa grade hot-formed steel, the composition and content of which are shown in Table 1 below, including 0.21wt% C, 0.23wt% Si, 1.15wt% Mn, 0.2wt% Cr, 0.02wt% Ti, 0.003wt% B, 0.1wt% Sn, and P≤0.015wt%, S≤0.005wt%, and the balance is Fe and unavoidable impurities. The preparation method thereof comprises the following steps:
[0039] (1) Preparing, smelting and casting into billets according to the set element mass percentages;
[0040] (2) heating the blank to 1200° C. for homogenization;
[0041] (3) hot rolling the homogenized billet, and controlling the final rolling temperature at 800°C;
[0042] (4) coiling at 650°C after hot rolling;
[0043] (5) Hot stamping is performed, specifically, the steel is heated to 930° C. and then kept at this temperature for 5 min, and then quenched to room temperature to obtain hot-formed steel.
[0044] Comparative Example 1
[0045] A 1500MPa grade hot-formed steel, the composition and content of which are shown in Table 1 below, includes 0.22wt% C, 0.25wt% Si, 1.2wt% Mn, 0.23wt% Cr, 0.018wt% Ti, 0.005wt% B, and P≤0.015wt%, S≤0.005wt%, and the balance is Fe and unavoidable impurities. The preparation method thereof includes the following steps:
[0046] (1) Preparing, smelting and casting into billets according to the set element mass percentages;
[0047] (2) heating the blank to 1200° C. for homogenization;
[0048] (3) hot rolling the homogenized billet, and controlling the final rolling temperature at 800°C;
[0049] (4) coiling at 650°C after hot rolling;
[0050] (5) Hot stamping is performed, specifically, the steel is heated to 930° C. and then kept at this temperature for 5 min, and then quenched to room temperature to obtain hot-formed steel.
[0051] Comparative Example 2
[0052] A 1500MPa grade hot-formed steel, the composition and content of which are shown in Table 1 below, includes 0.21wt% C, 0.24wt% Si, 1.25wt% Mn, 0.22wt% Cr, 0.025wt% Ti, 0.005wt% B, 0.2wt% Sn, and P≤0.015wt%, S≤0.005wt%, and the balance is Fe and unavoidable impurities. The preparation method thereof includes the following steps:
[0053] (1) Preparing, smelting and casting into billets according to the set element mass percentages;
[0054] (2) heating the blank to 1200° C. for homogenization;
[0055] (3) hot rolling the homogenized billet, and controlling the final rolling temperature at 800°C;
[0056] (4) coiling at 650°C after hot rolling;
[0057] (5) Hot stamping is performed, specifically, the steel is heated to 930° C. and then kept at this temperature for 5 min, and then quenched to room temperature to obtain hot-formed steel.
[0058] Comparative Example 3
[0059] A 1500MPa grade hot-formed steel, the composition and content of which are shown in Table 1 below, includes 0.22wt% C, 0.26wt% Si, 1.50wt% Mn, 0.18wt% Cr, 0.08wt% Ti, 0.003wt% B, and P≤0.015wt%, S≤0.005wt%, and the balance is Fe and unavoidable impurities. The preparation method thereof includes the following steps:
[0060] (1) Preparing, smelting and casting into billets according to the set element mass percentages;
[0061] (2) heating the blank to 1200° C. for homogenization;
[0062] (3) hot rolling the homogenized billet, and controlling the final rolling temperature at 800°C;
[0063] (4) coiling at 650°C after hot rolling;
[0064] (5) Hot stamping is performed, specifically, the steel is heated to 930° C. and then kept at this temperature for 5 min, and then quenched to room temperature to obtain hot-formed steel.
[0065] Comparative Example 4
[0066] A 1500MPa grade hot-formed steel, the composition and content of which are shown in Table 1 below, includes 0.20wt% C, 0.25wt% Si, 1.30wt% Mn, 0.05wt% Cr, 0.016wt% Ti, 0.005wt% B, and P≤0.015wt%, S≤0.005wt%, and the balance is Fe and unavoidable impurities. The preparation method thereof includes the following steps:
[0067] (1) Preparing, smelting and casting into billets according to the set element mass percentages;
[0068] (2) heating the blank to 1200° C. for homogenization;
[0069] (3) hot rolling the homogenized billet, and controlling the final rolling temperature at 800°C;
[0070] (4) coiling at 650°C after hot rolling;
[0071] (5) Hot stamping is performed, specifically, the steel is heated to 930° C. and then kept at this temperature for 5 min, and then quenched to room temperature to obtain hot-formed steel.
[0072] Comparative Example 5
[0073] A Sn-containing low hydrogen-induced delayed cracking sensitivity 1500MPa grade hot-formed steel, the composition and content of which are shown in Table 1 below, including 0.2wt% C, 0.27wt% Si, 1.4wt% Mn, 0.16wt% Cr, 0.015wt% Ti, 0.002wt% B, 0.02wt% Sn, and P≤0.015wt%, S≤0.005wt%, and the balance is Fe and unavoidable impurities. The preparation method thereof comprises the following steps:
[0074] (1) Preparing, smelting and casting into billets according to the set element mass percentages;
[0075] (2) heating the blank to 1200° C. for homogenization;
[0076] (3) hot rolling the homogenized billet, and controlling the final rolling temperature at 800°C;
[0077] (4) coiling at 650°C after hot rolling;
[0078] (5) Perform hot stamping, specifically heating to 800°C and then keeping the temperature for 5 minutes, and then quenching to room temperature to obtain hot-formed steel.
[0079] Table 1 - Composition and content of hot-formed steel in the present embodiment and comparative example
[0080]
[0081] Performance testing
[0082] 1. Tensile strength and elongation: The hot-formed steels of the examples and comparative examples were tested according to the standard of GB / T 228.1-2021 (Tensile test of metallic materials Part 1: Room temperature test method). 2. Experimental conditions for hydrogen-induced delayed cracking sensitivity: According to the standard of GB / T 39039-2020 (Evaluation method for hydrogen-induced delayed fracture of high-strength steel), all hot-formed steel samples of the examples and comparative examples were immersed in a mixed solution of 0.1 mol / L sodium hydroxide + 0.2 g / L thiourea for electrochemical hydrogenation for 24 hours at a current density of 1 mA / cm 2 Then, a slow strain rate tensile test was carried out with a tensile strain rate of 1×10 -5 / s. The hydrogen-induced delayed cracking sensitivity coefficient is equal to the loss of elongation before and after hydrogen charging. The lower the hydrogen-induced delayed cracking sensitivity, the better the hydrogen-induced delayed cracking resistance. The test results are shown in 2 below.
[0083] Table 2 - Performance test results of hot-formed steel of examples and comparative examples
[0084] Test items Tensile strength(MPa) Elongation(%) Hydrogen induced delayed cracking sensitivity (%) Example 1 1600 11.6 32 Example 2 1581 10.2 14 Comparative Example 1 1601 9.9 75 Comparative Example 2 1550 10.5 52 Comparative Example 3 1590 9.7 80 Comparative Example 4 1435 12.2 28 Comparative Example 5 1310 12.8 20
[0085] As shown in Table 2 and Figure 1 As shown, the present application can promote the formation of cementite and increase the content of pearlite in the hot-rolled plate by adding a proper amount of Sn element to the hot-formed steel, improve the stability of ε carbide in the hot-forming stage, improve the hydrogen trap ability of carbide, and effectively capture hydrogen atoms. Compared with the hot-formed steel in comparative example 1 to which no Sn element is added, the addition of a proper amount of Sn element in Examples 1-2 of the present application can effectively reduce the hydrogen-induced delayed cracking sensitivity of the material, and the hydrogen-induced delayed cracking sensitivity is ≤32%, which is reduced by 57%.
[0086] Secondly, compared with Comparative Example 2, the Sn content in Examples 1-2 of the present application is limited to 0.02wt%-0.1wt%. Adding too high a Sn content in Comparative Example 2 will segregate to the original austenite grain boundaries, reduce the grain boundary bonding force, affect the mechanical properties of the material and increase the sensitivity to hydrogen-induced delayed cracking.
[0087] In addition, compared with Examples 1-2, the Ti content in the material of Comparative Example 3 is too high, which will generate large-sized Ti-containing inclusions. Due to stress concentration, hydrogen will be enriched at the interface between the inclusions and the matrix, thereby causing hydrogen-induced delayed cracking. The Cr content in the material of Comparative Example 4 is too low, which will reduce the hardenability and the tensile strength of the material. The hot stamping temperature of Comparative Example 5 is lower than 900°C, and the material is in the two-phase region and is not completely austenitized. The subsequent quenching cannot obtain a full martensitic structure, which will greatly reduce the tensile strength.
[0088] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A Sn-containing low hydrogen-induced delayed cracking sensitivity 1500MPa grade hot-formed steel, characterized in that: The invention comprises the following components in mass fraction: C: 0.20wt%-0.23wt%, Si: 0.23wt%-0.27wt%, Mn: 1.0wt%-1.5wt%, Cr: 0.15wt%-0.25wt%, Ti: 0.015wt%-0.050wt%, B: 0.002wt%-0.005wt%, Sn: 0.01wt%-0.12wt%, P: ≤0.015wt%, S: ≤0.005wt%, and the balance is Fe and unavoidable impurities.
2. The Sn-containing low hydrogen-induced delayed cracking sensitivity 1500 MPa grade hot-formed steel according to claim 1, characterized in that: The mass fraction of Sn in the hot-formed steel is 0.02wt%-0.1wt%.
3. The Sn-containing low hydrogen-induced delayed cracking sensitivity 1500 MPa grade hot-formed steel according to claim 1, characterized in that: The invention comprises the following components in mass fractions: C: 0.2wt%, Si: 0.27wt%, Mn: 1.4wt%, Cr: 0.16wt%, Ti: 0.015wt%, B: 0.002wt%, Sn: 0.02wt%, P: ≤0.015wt%, S: ≤0.005wt%, and the balance is Fe and unavoidable impurities.
4. The Sn-containing low hydrogen-induced delayed cracking sensitivity 1500 MPa grade hot-formed steel according to claim 1, characterized in that: The invention comprises the following components in mass fractions: C: 0.21wt%, Si: 0.23wt%, Mn: 1.15wt%, Cr: 0.2wt%, Ti: 0.02wt%, B: 0.003wt%, Sn: 0.1wt%, P: ≤0.015wt%, S: ≤0.005wt%, and the balance is Fe and unavoidable impurities.
5. A method for preparing Sn-containing low hydrogen-induced delayed cracking sensitivity 1500MPa grade hot-formed steel according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) preparing ingredients according to a set element mass percentage, mixing and smelting, and then casting into a billet to obtain a billet; (2) heating the blank to perform homogenization treatment; (3) hot rolling the homogenized billet; (4) Coiling after hot rolling; (5) Hot stamping is performed, the heating temperature of hot stamping is 900°C-950°C, and then quenching is performed to room temperature to obtain hot-formed steel.
6. The method for preparing Sn-containing low hydrogen-induced delayed cracking sensitivity 1500 MPa grade hot-formed steel according to claim 5, characterized in that: In step (2), the heating temperature for homogenization treatment is 1180°C-1250°C.
7. The method for preparing Sn-containing low hydrogen-induced delayed cracking sensitivity 1500 MPa grade hot-formed steel according to claim 5, characterized in that: In step (3), the hot rolling process controls the final rolling temperature to be 780°C-880°C.
8. The method for preparing Sn-containing low hydrogen-induced delayed cracking sensitivity 1500 MPa grade hot-formed steel according to claim 5, characterized in that: In step (4), the coiling temperature is 620°C-700°C.
9. The method for preparing Sn-containing low hydrogen-induced delayed cracking sensitivity 1500 MPa grade hot-formed steel according to claim 5, characterized in that: In step (5), the hot stamping holding time is 3 min-5 min.
10. Use of the Sn-containing 1500 MPa grade hot-formed steel with low hydrogen-induced delayed cracking sensitivity as claimed in any one of claims 1 to 9 in the field of manufacturing automobile parts.